2011
DOI: 10.1021/jp204168s
|View full text |Cite
|
Sign up to set email alerts
|

Helical Superstructure and Charged Polarons Contributions to Optical Nonlinearity of 2-Methyl-4-nitroaniline Crystals Studied by Resonance Raman, Electron Paramagnetic Resonance, Circular Dichroism Spectroscopies, and Quantum Chemical Calculations

Abstract: The Raman excitation profiles of solid 2-methyl-4-nitroaniline (MNA) reveal several band enhancements by intermolecular and intramolecular charge transfer states. Calculated excited- and ground-state molecular geometries and excited state distortions qualitatively determined from Raman spectra indicate multiple vibrations leading to MNA dissociation. Also, overtones and combination tones can generate charged polarons, as detected by electron paramagnetic resonance after the exposure to 980 and 1550 nm laser di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The relative intensities were estimated by taking as the internal standard (100%) at each exciting line the integral intensity of the 1275 cm −1 band (stretching ν CN vibration) as in the case of MNA spectra. 11 The relative intensity of the ν NH stretching vibration band is enhanced by the 496.5 nm (20140 cm −1 ) laser line corresponding to the first electronic transition at 21630 cm −1 (Figure 8). The ν s NO 2 stretching at 1320 cm −1 and the δ NO 2 bending vibration at 809 cm −1 are reinforced by the 514.5 and 530.9 nm lines.…”
Section: Experimental and Computational Methodsmentioning
confidence: 97%
“…The relative intensities were estimated by taking as the internal standard (100%) at each exciting line the integral intensity of the 1275 cm −1 band (stretching ν CN vibration) as in the case of MNA spectra. 11 The relative intensity of the ν NH stretching vibration band is enhanced by the 496.5 nm (20140 cm −1 ) laser line corresponding to the first electronic transition at 21630 cm −1 (Figure 8). The ν s NO 2 stretching at 1320 cm −1 and the δ NO 2 bending vibration at 809 cm −1 are reinforced by the 514.5 and 530.9 nm lines.…”
Section: Experimental and Computational Methodsmentioning
confidence: 97%
“…2-Methyl-4-nitroaniline (2m4na) was the first organic molecule for which non-linear optical properties were revealed as it crystallizes without a center of symmetry (Levine et al, 1979). Since that time, second harmonic generation measurements and related studies in terms of optical activity were carried out for many organics including nitroaniline derivatives (Okwieka et al, 2008(Okwieka et al, , 2009Szostak et al, 2011). The crystal structure of 2m4na has been determined by X-ray (Ferguson et al, 2001;Howard et al, 1992) and neutron measurements (Whitten et al, 2006) which showed that the amino group is slightly pyramidal and the nitro group lies in the plane of the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the intermolecular charge transfer (via intermolecular hydrogen bonds, HBs), charged polarons (radical anions), conformational helical packing in crystal, vibrational anharmonicity, vibronic couplings and dynamical disorder (molecular motions) are additional factors which influence nonlinear response [2][3][4][5][6][7][8]. The dynamics of a system can be examined by temperature dependent fourier transform IR (FT-IR) and proton nuclear magnetic resonance ( 1 H NMR) spectroscopies where the activation energy and the correlation time of movement can be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a continuation of studies on optically nonlinear (NLO) benzene derivatives crystals such as meta-nitroaniline (m-NA) [3,4,8], 2-methyl-4-nitroaniline (MNA) [6,14,15], 4-isopropylphenol (4-IP) [16] and N-benzyl-2-methyl-4-nitroaniline (BNA) [7,17,18]. The earlier studies showed that the charged polarons (radical anions), dynamic disorder of phenyl ring and both (three) nitro and amine (methyl) substituents leads to the instantaneous helical superstructure in the m-NA [3,4] (MNA [6,15]) and contribute to the SHG in these crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation